Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1002/cld.709
|View full text |Cite
|
Sign up to set email alerts
|

Disease pathways and molecular mechanisms of nonalcoholic steatohepatitis

Abstract: http://aasldpubs.onlinelibrary.wiley.com/hub/journal/10.1002/(ISSN)2046-2484/video/11-4-reading-wegermann a video presentation of this article

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…In contrast, a multinational prospective study of 458 NAFLD patients by Vilar-Gomez et al reported that steatosis is significantly associated with a higher risk of death and liver-related complications, which aligns with the findings of this review, showcasing that NASH is associated with a significant burden and poor long-term prognosis [76]. It is important to note that because the exact cause of NAFLD and NASH is not yet understood, it is difficult to accurately assess the underlying factors for progression [57]. Therefore, further research into the cause of this disease is recommended to improve our understanding of disease progression and the key factors at play.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In contrast, a multinational prospective study of 458 NAFLD patients by Vilar-Gomez et al reported that steatosis is significantly associated with a higher risk of death and liver-related complications, which aligns with the findings of this review, showcasing that NASH is associated with a significant burden and poor long-term prognosis [76]. It is important to note that because the exact cause of NAFLD and NASH is not yet understood, it is difficult to accurately assess the underlying factors for progression [57]. Therefore, further research into the cause of this disease is recommended to improve our understanding of disease progression and the key factors at play.…”
Section: Discussionsupporting
confidence: 80%
“…The exact cause of NAFLD to NASH progression is unknown and is likely due to a complex interplay of environmental and genetic factors; however, certain health conditions, such as obesity, high blood pressure and diabetes, increase the risk of it developing [3, 4]. Numerous genetic, epigenetic and environmental contributors have recently been proposed as the cause of NAFLD and NASH, including smoking and altered copper bioavailability [57].…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, finding a reliable animal model of NASH to better understand the pathophysiology of the disease, to identify novel biomarkers and to find new targets for therapy, is still a scientific challenge. An ideal NASH animal model should mimic the full spectrum of the human disease [4]. In this regard, in the present study, we develop and characterize a new male-rat model of NASH that exhibits the major clinical characteristics of the human pathology: metabolic syndrome, hepatic steatosis, lipotoxicity, hepatic cell death, hepatic inflammation, hepatic fibrosis, and portal hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…In view of the increasing incidence of NAFLD worldwide, a large number of translational laboratories are focused on understanding new aspects of NASH pathophysiology, on discovering specific and non-invasive diagnostic biomarkers, and developing effective pharmacologic treatments [4]. Nevertheless, the lack of reliable NASH animal models remains a limitation for studying the disease and for developing new therapeutic strategies [5].…”
Section: Introductionmentioning
confidence: 99%
“…Tremendous progress has been made in our understanding of the mechanisms underlying non-alcoholic fatty liver disease (NAFLD) (1)(2)(3), including the identification of several molecular pathways impacting a number of cell types (hepatocytes, macrophages, stellate cells) and organ systems, ranging from the liver to adipose tissue, the gut, immune system, and kidney (4,5). Yet, few if any of these pathways explicitly involve skeletal muscle, the principal organ responsible for glucose disposal (6) and energy homeostasis (7), key processes that can impact the core pathogenesis of a systemic metabolic disease such as NAFLD (8).…”
Section: Introductionmentioning
confidence: 99%